Efficacy of defibrillator pads placement during ventricular arrhythmias, a before and after analysis. (May 2022) - Steinberg, Mikkel F.; Olsen, Jan-Aage; Persse, David; Souders, Chris M.; Wik, Lars
Abstract: Background: European resuscitation guidelines describe several acceptable placements of defibrillator pads during resuscitation of cardiac arrest. However, no clinical trial has compared defibrillation efficacy between any of the different pad placements. Houston Fire Department emergency medical system (EMS) used anterior-posterior (AP) defibrillator pad placement before becoming a study site in the circulation improving resuscitation care trial (CIRC). During CIRC, Houston Fire EMS used sternal-apical (SA) pad placement. Methods: Data from electronic defibrillator records was compared between a pre-CIRC dataset and patients in the CIRC trial receiving manual cardiopulmonary resuscitation (CPR). Only shocks from patients with initial ventricular fibrillation (VF) or pulseless ventricular tachycardia (VT) were included. Measured outcome was defibrillation efficacy, defined as termination of VF/VT. The general estimating equations model was used to study the association between defibrillation efficacy rates in the AP vs SA group. Results: In the pre-CIRC dataset, 207 included patients received 1023 shocks with AP pad placement, compared with 277 patients from the CIRC trial who received 1020 shocks with SA pad placement. There was no significant difference in defibrillation efficacy between AP and SA pads placement (82.1 % vs 82.2 %, p = 0.98). Conclusion: No difference was observed in defibrillation efficacy between AP and SA pad placement in this study. A randomized clinical trial may be indicated.